The combined use of admixtures for shrinkage reduction in one-part alkali activated slag-based mortars and pastes. (10th July 2020) - Coppola, L.; Coffetti, D.; Crotti, E.; Candamano, S.; Crea, F.; Gazzaniga, G.; Pastore, T.
Highlights: Effects of combined use of admixtures on one-part AAS were evaluated. The use of expansive agent with SRA can mitigate the high shrinkage of AAS. A linear correlation between shrinkage and moisture loss of admixed AAS was found. Abstract: Binders obtained by alkaline activation of ground granulated blast furnace slag (GGBFS) represent an interesting alternative to Portland cement to manufacture sustainable mortars and concretes. However, several issues prevent them to have a ready and wide marketplace, such as high-magnitude shrinkage and lack of knowledge about advanced admixtures to control and regulate their properties and desired performance. The purpose of this research is, thus, to evaluate the effect of the combined addition of ethylene glycol-based shrinkage reducing admixture (SRA), calcium oxide-based expansive agents (EA), methylcellulose (MC) and modified starch (MS) on fresh properties, elasto-mechanical parameters and shrinkage behaviour of one-part alkali activated slag-based (AAS) pastes and mortars at equal alkali content and silica modulus. Experimental data evidenced that the addition of methylcellulose, modified starch as well as ethylene glycol determines slower initial and final setting times respect to reference mixtures, while the CaO addition strongly reduces the setting times. Moreover, both SRA and EA reduce the elastic modulus (up to 5%) and mechanical strength of AAS mixtures (up to 20%) compared to pastes without admixtures. Results indicated that both the CaO-based expansive agents (EA) and ethylene glycol-based shrinkage reducing admixture (SRA) are effective to reduce the shrinkage of AAS mortars up to 50%. In particular, the combined use of expansive agents and SRA further limits the shrinkage, allowing to reach values close to 1000 μm/m after 150 days, typical of mortars based on Portland cement. Finally, a linear correlation between shrinkage and moisture loss was found, independently of the admixture used.